Estimating ultrasonic time-of-flight through echo signal envelope and modified Gauss Newton method. (December 2016) - Lu, Zhenkun; Yang, Cui; Qin, Donghong; Luo, Yuling; Momayez, Moe
Highlights: Hilbert transform is used to reduce the computational burden. Wavelet denoising technique is applied to improve the estimation accuracy. A Modified Gauss Newton (MGN) is proposed to overcome the weakness of the GN. The estimation of TOF is achieved with high accuracy even in low SNR. Abstract: The accurate estimation of ultrasonic Time-Of-Flight (TOF) is essential in ultrasonic non-destructive testing (NDT). In this paper, a novel method for TOF estimation through envelope is proposed. Firstly, the wavelet denoising technique is applied to the noisy echo to improve the estimation accuracy. Then, the Hilbert transform (HT) is used in ultrasonic signal processing in order to extract the envelope of the echo and to reduce the computational burden. Finally, the echo parameters are estimated by using a Modified Gauss Newton (MGN) based nonlinear Least Squares (LS) estimation method. And, a fast algorithm is adopted to estimate the parameters of M-superimposed echoes. Numerical simulation and experimental results have been carried out to show the performances of the proposed method in estimating TOF of ultrasonic signal.